Transfer of Mortgage Rights Resulting from Cession as a Land Administration Act: Peralihan Hak Tanggungan akibat Cessie sebagai Tindakan Administrasi Pertanahan - Krisnawaty, Krisnawaty; Muskibah, Muskibah; Abu Bakar, Firdaus (Fakultas Hukum Universitas Jambi, 2026)
This article analyzes the transfer of Mortgage Rights resulting from the assignment of receivables (cessie) within the framework of land and administrative law. The issue arises from differing interpretations of Article 16 paragraph (1) of the Mortgage Law concerning the phrase “by operation of law” in relation to the principle of publicity in land registration. Using a normative legal method with statutory and administrative law approaches, this study examines the juridical status of recording the transfer of Mortgage Rights at the Land Office. The findings show that although Mortgage Rights follow the receivable under the principle of accessorium sequitur principale, the transfer only gains external legal effect after being recorded in the land register. Such recording constitutes a land administrative act that fulfills the characteristics of a State Administrative Decision, as it is concrete, individual, and final, producing legal consequences for the new creditor. Therefore, legal certainty and protection depend on the legality of the administrative action carried out in accordance with the principles of legality and good governance.